Responses of the aleppo pine (Pinus halepensis Mill.) and the holm oak (Quercus ilex L. subsp. ballota (Desf.) Samp.) to the collection of overland runoffs through minicatchments in different Mediterranean environments (Forest Systems; Vol 15, No 2 (2006), 2008)
Water is one of the most limiting factors in the forestation of Mediterranean areas, so that the survival and development of these areas is always connected to the availability of water resources. The aim of this study is to assess the efficiency of a series of hydraulic structures linked to land preparation, called minicatchments, as runoff collectors meant to increase water availability in the forestation. In order to do so, the amount of overland runoff reaching every seedling, as well as the survival of the reforestation in four places with different climatic and edaphic characteristics have been assessed. Results obtained show how water availability depends both on the amount of water reaching the bank and on the physical properties of the land. The areas that have normally been considered more difficult to restore due to a de-structured profile, to the presence of superficial physical crusts and to a scarce vegetal cover are the ones showing a better response to the technique of runoff collection trough minicatchments.

Restauración del bosque mediterráneo: aplicación de modelos de restauración a los encinares. (II Congreso Forestal Español, 1997)
The activities in order to restore the mediterraneam forests have been constitued by the restoration of the structures and natural vegetation communities in order to preserve the water and soil in the drainage basins. A restoration of the vegetation covers in a drainage basin with hydrological and biological criteria have been projected, using sorne reforestation works in order to the best utilitation of the water resources and the conservation of the soil. The Quercus rotundifolia is one of the most extended species in the mediterranean area and it is apply for the forestation of the lands. This paper proposes a model of applied for its restoration. K.W.: